Correlation of duration of diabetes mellitus with bone mineral density in postmenopausal women - Khairuzzaman, M.; Abu Taher, M.; Daharul Islam, M.; Jahedul Islam, M. (International Journal of Research in Medical Sciences, 2025)
Background: Osteoporosis and type 2 diabetes mellitus commonly coexist in postmenopausal women, both increasing morbidity and fracture risk. Despite often normal or elevated bone mineral density, individuals with T2DM face a paradoxically higher fracture risk. This study aimed to assess the correlation between the duration of T2DM and BMD in postmenopausal women. Methods: This cross-sectional study was conducted in the Medicine Department of Sir Salimullah Medical College and Mitford Hospital from July 2023 to June 2024. A total of 120 postmenopausal women with T2DM were enrolled according to predefined criteria. Data were analyzed using SPSS 22.0, with a p<0.05 considered statistically significant. Results: Duration of diabetes demonstrated a significant negative correlation with BMD. T-scores showed strong inverse relationships at both the femoral neck (r =-0.649, p<0.001) and lumbar spine (r=-0.724, p<0.001). Similarly, Z-scores were negatively correlated at the femoral neck (r=-0.521, p<0.001) and lumbar spine (r=-0.540, p<0.001). Comparison of treatment modalities revealed no significant differences: women on oral agents had femoral neck and lumbar spine T-scores of -2.51±0.96 and -3.12±1.50, while those on oral agents plus insulin had scores of -2.94±1.17 and -3.54±1.52, respectively (p>0.05). Conclusions: Longer duration of T2DM is significantly associated with lower BMD in postmenopausal women, particularly at the femoral neck and lumbar spine. Treatment modality did not significantly influence BMD outcomes.